Wykładnia celowościowa: [Teleological interpretation] (Studia Prawnicze / The Legal Studies, 1985)
The article analyses teleological interpretation in the decision of the Civil Law Division and Labour Law and Social Insurance Division of the Supreme Court. We may distinguish three stages of teleological interpretation: a) to determine the aim of a legal text, b) to establish a relation between one of alternative meanings of the text and realization of the assigned aim, c) to choose the meaning as the right meaning of the interpreted legal text. The author analyses those three states of teleological interpretation in the decisions of the Supreme Court. Special attention has been paid to the way of determining aims of legal texts, kinds of aims, relation between teleological interpretation and linguistic interpretation, relation between certain meaning assigned to the legal text and realization of the aim of the text, role of scientific knowledge and common sense knowledge in teleological interpretation.Then the author points to the differences between teleological interpretation of legal texts and practical conclusions in the field of technics and technology.